Content analysis of the crisis management efforts of Singapore Airlines in the SQ006 crash. - Chua, Teresa Mei Hong. (2008)
Through the content analysis of two English dailies, The Straits Times and The Taipei Times, Singapore Airlines' public relations efforts were evaluated.